Investigation and verification on seismic behavior of precast concrete frame piers used in real bridge structures: Experimental and numerical study. (1st January 2018) - Qu, Hongya; Li, Tiantian; Wang, Zhiqiang; Wei, Hongyi; Shen, Jiawei; Wang, Hao
Highlights: Seismic behavior of precast concrete frame piers is verified for real applications. Two connection types used in the frame piers are investigated for the first time. Tie beam and cap beam structure systems of the frame piers are compared. Bond-slip effect and joint region behavior optimize the numerical results. Abstract: In this study, quasi-static cyclic test was conducted for three 1/3-scale specimens of different precast concrete frame pier structure systems of an urban viaduct in Shanghai, China. Various connection deployment strategies were utilized for the specimens, in order to verify these precast concrete frame piers used in the real structure. Two of the specimens were of the same cap beam design, while the third one was with tie beam. The two frame piers with cap beam had the same column-footing connection (grouted splice sleeve coupler), but the column-cap connections were grouted splice sleeve coupler and grouted corrugated duct connection, respectively. The frame pier with cast-in-place tie beam, however, only kept the grouted splice sleeve coupler for column-footing connection. The cyclic test results showed similar seismic behavior of the two specimens with cap beam, whereas the specimen with tie beam exhibited less energy dissipation capacity. This indicated that the seismic performance differences among the specimens are mainly caused by different structure systems, and the two types of the connections behave similarly with little damage. Finite element models that were optimized by considering joint region behavior and bond-slip phenomena showed good agreement with the test results.